Students Stress in Learning English on 2rd Semester at the Faculty of Teacher Training and Education (FKIP) Batanghari University of Jambi Academic Year 2017/2018 - Kartika Dewi; Nurul Fitri (JELT: Journal of English Language Teaching, 2017)
AbstractStress is unsatisfactory situations of life where people want to change it for the better one with the emotions come and go with circumstances’ changing. Learning English is the process to know more about English capability which develops in a human. The purposes in this research want to types of the stress that students feel in learning English on 2rd Semester at the Faculty of Teacher Training and Education (FKIP) Batanghari University of Jambi Academic Year 2017/2018. The researcher where numerical data used in order to analyze the gathered information is called quantitative research. The population of the research is 40 students and the samples are 20 students. The data collected by questionnaire. Then, Questionnaire used Scale likert with data ordinal. The result of this research are, 20% of students stress affects sleep because students tired when who activities in campus. 34 5 high score is behavior of students, 31% is Personal habit and 15% low score is emotional. There were ways done by students to disappear their stress is pray to God. Sharing problem solve with parents, family, close friend and so on. All of students activities to lose the feeling stress. Some way alternative disappear their stress is do activities to construct lively release and always positive thinkingKeyword:   Students Stress, Learning English